2016
DOI: 10.1007/978-3-319-39225-7_8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Low Level of Agreement Among Reviewers in a Code Review Process

Abstract: Part 1: Full PapersInternational audienceSoftware code review systems are commonly used in software development. In these systems, many patches are submitted to improve the quality. To verify the quality, voting is commonly used by contributors; however, there still exists a major problem, namely, that reviewers do not always simply reach a broad agreement. In our previous study, we found that consensus is not usually reached, implying that an individual reviewer’s final decision usually differs from that of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Recently, Hirao et al [16] studied patches with divergent review scores and found that 15%-37% of patches that receive multiple review scores suffer from divergent scores. Furthermore, [8] showed that a low level of agreement is more likely to take a longer reviewing time and discussion length. Thongtanunam et al [21] investigated patches that do not attract reviewers, not discussed, and receive slow initial feedback.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hirao et al [16] studied patches with divergent review scores and found that 15%-37% of patches that receive multiple review scores suffer from divergent scores. Furthermore, [8] showed that a low level of agreement is more likely to take a longer reviewing time and discussion length. Thongtanunam et al [21] investigated patches that do not attract reviewers, not discussed, and receive slow initial feedback.…”
Section: Related Workmentioning
confidence: 99%
“…2) Divergent reviewers (DR): A code patch under review can suffer from divergent reviewers when reviewers cannot agree on the final evaluation by providing conflicting reviews and scores [16]. DR can lead to several problems in the review process including developer abandonment [11], poor team performance [29] and slow integration processes [8].…”
Section: Mcra: a Catalog Of Mcr Anti-patternsmentioning
confidence: 99%
“…In the context of tool-based reviews, researchers have investigated the relationship between code change acceptance or response time and features of the changed code and authors [41], as well as the agreement among reviewers [22]. Qualitative investigations have been also conducted to define what constitutes a good code review according to industrial [11] and OSS developers [26].…”
Section: Idmentioning
confidence: 99%
“…Rigby et al [17] found that six large-scale OSS projects needed approximately one month to integrate a patch. Reviewers may disagree with one another and take even longer for discussion [18]. The process also requires identifying appropriate reviewers for each patch.…”
Section: A Patch Author Submits a Patch To Gerrit Code Reviewmentioning
confidence: 99%